Clinical characteristics of non-critically ill patients with novel coronavirus infection (COVID-19) in a Fangcang Hospital. (August 2020) - Wang, X.; Fang, J.; Zhu, Y.; Chen, L.; Ding, F.; Zhou, R.; Ge, L.; Wang, F.; Chen, Q.; Zhang, Y.; Zhao, Q.
Abstract: Objectives: To describe the clinical characteristics of patients in a Fangcang Hospital. Methods: Non-critically ill individuals with positive SARS-CoV-2 RT-PCR tests admitted between 7 February and 12 February 2020 to Dongxihu Fangcang Hospital, which was promptly constructed because of the rapid, exponential increase in COVID-19 patients in Wuhan, China, were included; clinical course through to 22 February was recorded. Results: A total of 1012 non-critically ill individuals with positive SARS-CoV-2 RT-PCR tests were included in the study. Thirty (of 1012, 3.0%) individuals were asymptomatic on admission. During hospitalization, 16 of 30 (53.3%) asymptomatic individuals developed different symptoms. Fourteen of 1012 patients (1.4%) remained asymptomatic from exposure to the end of follow up, with a median duration of 24 days (interquartile range 22–27). Fever (761 of 1012, 75.2%) and cough (531 of 1012, 52.4%) were the most common symptoms. Small patchy opacities (355 of 917, 38.7%) and ground-glass opacities (508 of 917, 55.4%) were common imaging manifestations in chest CT scans. One hundred patients (9.9%) were transferred to designated hospitals due to aggravation of illness. Diarrhoea emerged in 152 of 1012 patients (15.0%). Male, older age, diabetes, cardiovascular diseases, chills, dyspnoea, So 2 value of ≤93%, white blood cell counts of >10 × 10 9 /L and large consolidated opacities on CT images were all risk factors for aggravation of illness. Conclusions: Non-critically ill individuals had different clinical characteristics from critically ill individuals. Asymptomatic infections only accounted for a small proportion of COVID-19. Although with a low incidence, diarrhoea was observed in patients with COVID-19, indicating the possibility of faecal–oral transmission.